2017
DOI: 10.1104/pp.17.00489
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Collection of Mutant Tomato Lines Using Pooled CRISPR Libraries

Abstract: The high efficiency of clustered regularly interspaced short palindromic repeats (CRISPR)-mediated mutagenesis in plants enables the development of high-throughput mutagenesis strategies. By transforming pooled CRISPR libraries into tomato (), collections of mutant lines were generated with minimal transformation attempts and in a relatively short period of time. Identification of the targeted gene(s) was easily determined by sequencing the incorporated guide RNA(s) in the primary transgenic events. From a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
115
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 57 publications
1
115
2
Order By: Relevance
“…More importantly, Jacobs et al (2017) were able to establish an association between the developmental phenotypes observed in T 0 plants and the mutations in the targeted genes. They demonstrated that mutations in a homolog of an Arabidopsis boron efflux transporter caused boron-deficiency phenotypes in tomato, defining a gene function in a single generation (Jacobs et al, 2017). Such a task would not be possible to complete in a generation using traditional mutagenesis approaches.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…More importantly, Jacobs et al (2017) were able to establish an association between the developmental phenotypes observed in T 0 plants and the mutations in the targeted genes. They demonstrated that mutations in a homolog of an Arabidopsis boron efflux transporter caused boron-deficiency phenotypes in tomato, defining a gene function in a single generation (Jacobs et al, 2017). Such a task would not be possible to complete in a generation using traditional mutagenesis approaches.…”
mentioning
confidence: 91%
“…In a pilot study in tomato, Jacobs et al (2017) developed a CRISPR/Cas9 plasmid library that targets 54 immunity-associated leucine-rich repeat subfamily XII genes. From a single transformation with this CRISPR/Cas9 library, they were able to identify heritable mutations in 15 out of 54 genes.…”
mentioning
confidence: 99%
See 3 more Smart Citations